2011
DOI: 10.2174/157489011794578419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doxycycline on Atherosclerosis: From Bench to Bedside

Abstract: Matrix metalloproteinases (MMPs) have a pivotal role in the natural history of atherosclerosis and its cardiovascular consequences. Non-selective MMP inhibition with doxycycline appears as a potential strategy to reduce the residual risk observed in patients already at intensive lipid lowering strategies. However, specific MMPs have different and even contradicting roles in the natural history of atherosclerosis, rendering broad spectrum MMP inhibition an important yet somewhat simplistic approach towards resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 155 publications
(190 reference statements)
0
7
0
1
Order By: Relevance
“…Doxycycline is also beneficial in a mouse model of oculopharyngeal muscular dystrophy (37). Doxycycline and related molecules produce a large number of molecular and cellular changes in mammalian cells and tissues (18,(38)(39)(40)(41). In Lama2 2/2 skeletal muscle, doxycycline treatment may be beneficial by reducing inflammation and cell death (18).…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline is also beneficial in a mouse model of oculopharyngeal muscular dystrophy (37). Doxycycline and related molecules produce a large number of molecular and cellular changes in mammalian cells and tissues (18,(38)(39)(40)(41). In Lama2 2/2 skeletal muscle, doxycycline treatment may be beneficial by reducing inflammation and cell death (18).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that doxycycline attenuates heart mechanical dysfunction and reduces inflammation in patients with coronary artery disease (CAD) [51]. In addition to its potential plaque stabilization in acute coronary syndromes properties, doxycycline shows promise in preventing ischemia-reperfusion injury and left ventricular remodeling [52]. Furthermore, clinical study demonstrated that doxycycline therapy led to downregulation of MMPs, dampening cardiac inflammation, and reduction of secondary myocardial infarction (MI) risk in coronary bypass patients [53].…”
Section: Biological Inhibitors Of Mmpsmentioning
confidence: 99%
“…Percutaneous transluminal coronary angioplasty (PTCA) is the prominent treatment modality for severe CAD blockage, and drug eluting stents (DES) are often used to support the arterial wall, treat flow-limiting coronary stenosis, and reduce the risk of restenosis. However, DES or bare metal stents suffer from several limitations such as the presence of permanent metal within the artery, incomplete stent apposition, and late instent thrombosis and restenosis 2 . Drug eluting balloons (DEB) are an alternative to DES particularly in conditions where stent use might not be optimal, such as at vessel bifurcations and small tortuous vessels 3 .…”
Section: Introductionmentioning
confidence: 99%